Bellodi's 'Saluto delle armi' re-examined - Lampugnani, Raffaele (Spunti e Ricerche, 2016)
A recent re-publication of the English translation of Il giorno della civetta was reviewed in The Observer on July 2001 by John Dickie who welcomed it as a "long unavailable translation of some of Sciascia's best work," and one in which in the critic's view is well deserving to be "rediscovered by an Anglophone readership. " The review is noteworthy in that it focuses on Sciascia's at times awkward criticism of the Mafia and of corruption in government, a topic which is still disturbing forty years after the first edition of the novel.